MARKETING COMMUNICATION STRATEGY OF HYUNDAI MOTOR INDONESIA ELECTRIC VEHICLE - Shafira Fitriani Putri; Tangguh Okta Wibowo; Rayhani Jastika; Sean Nalendra Hakim; Stefanie Liman (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The interest in purchasing electric vehicles in Indonesia is influenced by high prices, inadequate charging infrastructure, and low public awareness of their benefits. However, the market potential for electric vehicles in Indonesia remains promising due to growing environmental consciousness and the government's target to reduce carbon dioxide emissions. Currently, Hyundai and Wuling are the only car manufacturers with electric vehicle factories in Indonesia. This research aims to explain the marketing communication strategy of Hyundai Motor Indonesia's electric vehicle. This research focuses on explaining Hyundai Motor Indonesia's marketing communication strategy in introducing their electric vehicle. The research uses a case study method on Hyundai Motor Indonesia by conducting observations and interviews as data collection methods. The results showed that Hyundai Motor Indonesia uses various promotional channels as a medium for their electric vehicle campaign. Through the use of various promotional channels, focus on public awareness, market segmentation, emphasis on environmental and economic advantages, and special after-sales programs, Hyundai is trying to increase public awareness, understanding, and buying interest in electric vehicle.